Pharmacology of biosimilar candidate drugs in Rheumatology: a literature review - Araújo, Fernando (2017)
Objective: To review current evidence concerning pharmacology of biosimilar candidates to be used in rheumatology. Methods: A PubMed search up to August 2013 was performed using relevant search terms to include all studies assessing pharmacological properties of biosimilar candidates to be used in rheumatology. Data on study characteristics, type of intervention, pharmacokinetics (PK), pharmacodynamics (PD) and bioequivalence ratios was extracted. Results: Of 280 articles screened, 5 fulfilled our inclusion criteria. Two trials, PLANETAS and PLANETRA, compared CT-P13 and infliximab in patients with active ankylosing spondylitis and rheumatoid arthritis, respectively PK bioequivalence was demonstrated in the phase 1 PLANETAS trial by highly comparable area under the curve (AUC) and maximum drug concentrations (Cmax), whose geometric mean ratios fell between the accepted bioequivalence range of 80-125%. Equivalence in efficacy and safety was demonstrated in the phase 3 PLANETRA trial. Two phase 1 trials comparing etanercept biosimilar candidates TuNEX and HD203 in healthy volunteers showed a high degree of similarity in AUC and Cmax, with respective geometric mean ratios between PK bioequivalence range. The last included trial referred to GP2013, a rituximab biosimilar candidate, which demonstrated PK and PD bioequivalence to reference product in three different dosing regimens in cynomolgus monkeys. Conclusion: Infliximab, etanercept and rituximab biosimilar candidates have demonstrated PK bioequivalence in the trials included in this review. CT-P13 has recently been approved for use in the European market and the remaining biosimilar candidates are currently being tested in patients with rheumatoid arthritis.